Analisis Kebahasaan dari Film Habibie Ainun 3 Karya Ifan Ismail dalam Kajian Semiotika Roland Barthes - Muhammad Farich Nizami; Elvi Esya Ananta; Nova Ayu Rahmawati; Hanief Irfan Jodi Prabowo; Yani Evi Asih; Eni Nurhayati (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
The film Habibie & Ainun 3 is a 2019 Indonesian romantic biographical film directed by Hanung Bramantyo and written by Ifan Ismail. This film is a continuation of Rudy Habibie (2016), a prequel to Habibie & Ainun, as well as the third film in the Habibie & Ainun series. If Rudy Habibie tells the story of young Habibie, then Habibie & Ainun 3 tells the story of young Ainun. This article aims to describe the film Habibie & Ainun. In this film we will analyze language. Linguistics are the elements contained in a language, whether spoken or written. All matters related to language are called linguistics. Meanwhile, linguistic rules are definite rules, propositions, or guidelines used in language. This film is being analyzed using a descriptive qualitative approach. The method of data acquisition employed is documentation, which consists of listening and taking notes. Based on the results of the analysis, a variety of language styles were found which showed comparative language styles, conflicting language styles, satirical language styles, affirmative or repetition language styles.